EXPERIMENTAL STUDY ON WORK HARDENING OF TITANIUM ALLOY BY MILLING WAYS AND TOOL WEAR - CHEN MingHua; HU Jin; YANG HouChuan; DU XiaoWei (Jixie qiangdu)
Experiments on the titanium alloy Ti-1023（ Ti-10V-2Fe-3Al） work hardening and work hardening layer depth was studied by down or up milling,first milling or quadratic milling in a new tool or the wear tool. The results show that titanium alloy Ti-1023 is milled in carbide cutting tools,down milling in work hardening and work hardening layer depth is smaller than up milling,new tool in work hardening is smaller than wear tool,the work hardening layer depth is less than 25 μm in new tool; the work hardening layer depth is up to 81 μm and quadratic milling causes the machined surface softening in case of tool flank wear VB = 0. 3 mm.